Digilantism: an analysis of crowdsourcing and the Boston Marathon bombings - Nhan, Johnny (The British journal of criminology, 2017)
This paper explores the aftermath of the Boston Marathon bombing incident and how members of the general public, through the online community Reddit, attempted to provide assistance to law enforcement through conducting their own parallel investigations. As we document through an analysis of user posts, Reddit members shared information about the investigation, searched for information that would identify the perpetrators and, in some cases, drew on their own expert knowledge to uncover clues concerning key aspects of the attack. Although it is the case that the Reddit cyber-sleuths’ did not ultimately solve this case, or provide significant assistance to the police investigation, their actions suggest the potential role the public could play within security networks.